Comparative effectiveness evidence from the spine patient outcomes research trial: surgical versus nonoperative care for spinal stenosis, degenerative spondylolisthesis, and intervertebral disc herniation. - Tosteson, Anna N.A.; Tosteson, Tor D.; Lurie, Jon D.; Abdu, William; Herkowitz, Harry; Andersson, Gunnar; Albert, Todd; Bridwell, Keith; Zhao, Wenyan; Grove, Margaret R.; Weinstein, Milton C.; Weinstein, James (Spine, 2011)
Study Design. Cost-effectiveness analysis of a randomized plus observational cohort trial. Objective. Analyze cost-effectiveness of Spine Patient Outcomes Research Trial data over 4 years comparing surgery with nonoperative care for three common diagnoses: spinal stenosis (SPS), degenerative spondylolisthesis (DS), and intervertebral disc herniation (IDH). Summary of Background Data. Spine surgery rates continue to rise in the United States, but the safety and economic value of these procedures remain uncertain. Methods. Patients with image-confi rmed diagnoses were followed in randomized or observational cohorts with data on resource use, productivity, and EuroQol EQ-5D health state values measured at 6 weeks, 3, 6, 12, 24, 36, and 48 months. For each diagnosis, cost per quality-adjusted life year (QALY) gained in 2004 US dollars was estimated for surgery relative to nonoperative care using a societal perspective, with costs and QALYs discounted at 3% per year. Results. Surgery was performed initially or during the 4-year follow-up among 414 of 634 (65.3%) SPS, 391 of 601 (65.1%) DS, and 789 of 1192 (66.2%) IDH patients. Surgery improved health, with persistent QALY differences observed through 4 years (SPS QALY gain 0.22; 95% confi dence interval, CI: 0.15, 0.34; DS QALY T